The Implementation of Interactive Media to Improve Student Achievement in Lighting and Signaling Systems - Febrianti, Alfira Dwi; Widjanarko, Dwi; Abdurrahman, Abdurrahman (Journal of Vocational and Career Education, 2024)
Students’ limited understanding of lighting systems and signaling lamps is attributed to conventional teaching methods, insufficient practical tools, and the absence of interactive learning media. This study aimed to develop, assess the feasibility, and test the effectiveness of web-based interactive learning media on the subject. The method applied Research and Development (R&D) with the ADDIE development model. The research design adopted a Pretest-Posttest Control Group Design. The validation results indicated that the media was highly feasible for use, as shown by maximum eligibility scores. The effectiveness test, comparing the control and experimental groups, showed a significant difference. The improvement in students’ learning outcomes fell into the moderate category. Therefore, this learning media was proven to be both feasible and effective in enhancing students’ achievement on the topic of lighting systems and signaling lamps.